A Case Report of Double Primer Cancer: Malignant Phyllodes Tumor and Invasive Ductal Carcinoma - Lauraine Wijayaningtyas Sinuraya; Kristanto Yuli Yarso (Indonesian Journal of Cancer, 2022)
Introduction: Multiple primaries have been reported in patients with breast cancer in the range of 4.1% to 16.4%. This report followed the standard Surgical Case Report (SCARE) and discussed two histologically distinct breast cancer malignancies. This paper also explored the risk factor, pathogenesis, treatment, and prognosis of multiple primary malignancies in the same organs, especially in the breasts.Case Presentation: The patient was a 45-year-old woman with a lump in the left and right breasts for five years. The patient claimed that the lump was enlarged and painless. The tumor size of the left breast was 3 x 2 x 3 cm, the right breast was 4 x 2 x 4 cm, and the patient had no enlargement of lymph nodes. The patient underwent a biopsy examination of the left breast showing invasive ductal carcinoma NST (No Special Type) 3rd grade with LV1 (+). The biopsy examination of the right breast showed malignant phyllodes tumor. Thus, the patient must undergo chemotherapy and mastectomy as definitive therapy. The patient has already completed the treatment and is currently under evaluation.Conclusion: This report looked for the rare case of double primary malignancies in the breasts. It highlighted double primary cancers starting to increase these days but in a particular way because it happens in the same organ, the breasts. However, medical literature rarely presented a synchronous malignancy case, prompting the publishing of this case. With improved cancer treatment and more prolonged survival, the number of patients with double cancers is increasing.